PENGARUH BELANJA PEMERINTAH PUSAT (BELANJA MODAL, BELANJA BARANG, DAN BELANJA BANTUAN SOSIAL) TERHADAP PERTUMBUHAN EKONOMI (PDRB) PEMERINTAH PROVINSI TAHUN 2014-2019 - slamet widodo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2020)
In order to carry out concurrent government affairs in regional level, thecentral government allocates spending to support investment growth in theregions through capital expenditure, goods expenditure and social assistancespending. This capital accumulation is intended to increase the output of localgovernment goods and services which in turn will increase regional economicgrowth.The purpose of this study is to analyze the Impact of Central GovernmetExpenditure (Capital, Goods, and Social Assistance Expenditures) towards GrossRegional Domestic Product (PDRB) of provincial government for the period of2014-2019. Data used was taken from BPS, the Ministry of Finance, and otherrelevant agencies. Analysis tools using data panel regression with fixed effectmodel. The results of the analysis shows that only capital expenditure haspositive effect on PDRB, and social assistance expenditure has negative effecton PDRB. While goods expenditure variable is excluded from the model, since itnot met the multicollinearity test